The Influence of Marketing Strategy on Increasing Customer Loyalty at Alfamart Sorong City - Edwar, Rizka Cintya (LLDIKTI Wilayah 1 Sumatera Utara, 2025)
This study aims to examine the influence of marketing strategies on customer loyalty at Alfamart in Sorong City. Employing a quantitative research design, data were collected from 100 Alfamart customers using a structured questionnaire based on a Likert scale. The data were analyzed using simple linear regression through SPSS version 20. The findings reveal that marketing strategies have a positive and statistically significant impact on customer loyalty. This indicates that the more effectively Alfamart implements its marketing strategies—such as promotions, pricing, and customer engagement—the higher the level of customer retention and repeat purchases. The significance of this study lies in its contribution to the understanding of customer loyalty drivers in the modern retail sector, particularly within the context of Indonesia’s growing convenience store market. It provides empirical evidence for business practitioners regarding the importance of aligning marketing initiatives with customer expectations. However, the study is limited by its scope, focusing only on one retail brand in a specific geographic area, which may limit the generalizability of the findings. Future research is recommended to include comparative studies across different retail chains and regions to enhance external validity